Synergistic effect of fluoride and sodium hexametaphosphate in toothpaste on enamel demineralization in situ - Camara, Danielle Mendes da[UNESP]; Pessan, Juliano Pelim [UNESP]; Francati, Tamires Melo [UNESP]; Santos Souza, José Antonio [UNESP]; Danelon, Marcelle [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP] (Elsevier B. V., 2015)
To evaluate the effect of a fluoride dentifrice containing sodium hexametaphosphate (HMP) on enamel demineralization in situ. This double-blind and cross-over study consisted of 3 phases (7 days each) in which 12 volunteers wore intraoral appliances containing four enamel bovine blocks. Specimens were treated (3×/day) with placebo (no F or HMP), 1100ppm F (1100F) and 1100F plus HMP1% (1100F-HMP1%) toothpastes, and the cariogenic challenge was performed using a 30% sucrose solution (6×/day). Final surface hardness, the percentage of surface hardness loss (%SH), the integrated loss of subsurface hardness (ΔKHN), as well as enamel calcium (Ca), phosphorus (P) and firmly-bound fluoride (F) were determined. Also, biofilm formed on the blocks were analyzed for F, Ca, P and insoluble extracellular polysaccharide (EPS) concentrations. Data were submitted 1-way ANOVA, followed by Student-Newman-Keuls' test (p<0.05). 1100F-HMP1% promoted the lowest %SH and ΔKHN among all groups (p<0.001). The addition of HMP1% to 1100F did not enhance enamel F uptake, but significantly increased enamel Ca concentrations (p<0.001). Similar EPS concentrations were seen for 1100F-HMP1% and 1100F groups (p>0.05). All the groups were supersaturated with respect to HA. However, only 1100F-HMP1% group was supersaturated with respect to CaF2 (p<0.05). The ionic activities of F(-), CaF(+) and HF(0) for the 1100F-HMP1% group were the highest among all groups (p<0.001). The addition of HMP1% to a conventional toothpaste significantly reduces enamel demineralization in situ when compared to 1100F. This dentifrice could be a viable alternative to patients at high risk of caries.
Keywords: Demineralization; Dental enamel; Dentifrices; Fluorides; Polyphosphates